Test the Quality of Petai Seed Flavor (Parkia speciosa Hassk.) Fermentation Results Using Tempe Yeast - Sity Sarroh; Dezi Handayani; Dwi Hilda Putri (Serambi Biologi, 2019)
Abstract. Petai plants (Parkia speciosa Hassk.) Are thought to originate from Malaysia. The most important part of the petai plant to use is the seeds. Petai seeds contain hexathionine, tetrathiane, trithiolane, pentathiopane, pentathiocane, and tetrathiepane which cause the petai to emit a smell of smell. One way to reduce the smell of smell in petai is to do fermentation. Benefits of fermented food products are for preservation, enhancing taste, and for producing new products. This study aims to find out whether from color, texture, aroma can be accepted by the community. This research was conducted at the Research Laboratory and Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences, Padang State University from October 2018 to March 2019. The data of this study were obtained from questionnaires tested using hedonic tests (preferences) and presented in the form of percentages. The results of this study showed that for color 74% while the criteria did not like 64%, for texture as much as 72% of those who liked and who did not like 52%, and for aroma 58%, while those who did not like 46%, for flavor taste of tempai petai seeds 66% while those who don't like 32%. The physical characteristics of tempeh are in accordance with the criteria of SNI 3144: 2009, namely: having a normal odor (typical tempe), normal color (white), compact texture, and normal taste (typical taste of tempe and not foreign).Keywords: Petai, Organoleptic,  Fermentation